Theory of electric field effect on the optical properties of elliptical quantum wires - Holovatska, N.H.; Yarema, V.V.; Holovatsky, V.A. (Kyiv: LLC APF POLYGRAPH SERVICE, 2023)
Modern technologies allow the growth of semiconductor quantum wires with various cross-sectional shapes. Theoretical studies are mainly carried out for cylindrical quantum wires, as exact solutions of the Schrödinger equation exist in this case. Wave functions are obtained analytically using Bessel functions, enabling their use in constructing solutions for more complex problems.
Keywords: quantum wire, semiconductor, quasiparticle, electron